Effective wound healing agents based on N-alkenylimidazole zinc complexes derivatives: future prospects and opportunities - Svetlana A. Lebedeva; Pavel A. Galenko-Yaroshevsky (Jr.); Tatiana V. Fateeva; Sergey S. Pashin; Nataliya R. Pashina; Irina B. Nektarevskaya; Andrey V. Zadorozhniy; Olga V. Shelemekh; Marina Yu. Ravaeva; Elena N. Chuyan; Lusine O. Alukhanyan; Tereza R. Glechyan; et al. (Belgorod National Research University, 2023)
Introduction: The therapeutic effect of commercially available domestic and foreign drugs for the treatment of various skin injuries is far from optimal. These drugs have no universal effects, but cause pronounced side reactions. There is a clear demand for development of innovative wound-healing drugs with antimicrobial properties, which increase the natural protective function of the skin. Pharmaceutical compounds with zinc nanoparticles have been increasingly recognized as a promising therapeutic direction. These drugs can easily penetrate into damaged tissues and stimulate metabolic processes. Zinc complexes with imidazole derivatives are of a particular interest. Imidazole acts as a structural fragment of many natural physiologically active compounds, thus providing targeted delivery of this essential trace element into the wound for inclusion in the multicascade mechanism of wound healing. The aim of the study: to provide experimental evidence for effects of recently developed zinc complexes with N-alkenylimidazole as wound healing agents. Materials and Methods: Wound-healing effects of six 1% gels containing distinct N-alkenylimidazole zinc complexe derivatives based on the Na-carboxymethylcellulose (Na-CMC) were comparatively studied in 128 outbred white rats of both genders. The Na-CMC-based Zinc Sulfate 1% gel, Methyluracil and Solcoseryl served as reference drugs. After performing the local tolerance study of zinc complexes, linear and planar sterile wounds of comparable size were inflicted in anesthetized animals. The degree of healing was evaluated on the day 8 and day 28 after the treatment start by wound sizes and histological examination of inflammatory response, epithelization, granulation tissue, angiogenesis, and necrosis. The skin microcirculation system was evaluated using the laser Doppler Flowmetry (LDF), whereby the blood flow indicators were recorded 30 and 60 minutes after intraperitoneal administration of the trial compound. The antimicrobial activity of the zinc compounds was determined in vitro by means of their minimum inhibitory concentration suppressing the bacteria and fungi growth using the double serial dilution method in liquid culture media. The statistical data processing was performed using the Statistica 12 software package. Results and Discussion: In the linear wound model, all animals treated with either of six experimental zinc compounds showed almost complete reduction in wound size (92-100%, p<0.05) on the day 8, significantly exceeding the wound healing in the control animals (reduction by 67-88 %, p<0.05) and effects of the reference drugs (reduction by 83-86%, p<0.05). In the planar wound model, the most significant wound healing effect was reached by using the gel containing N-isopropenylimidazole zinc diacetate (encoded as Pilim-1). The respective histological examination showed signs of complete epithelialization, absence of destructive changes in the epidermis, restoration of skin appendages and presence of mature granulation tissue. Intraperitoneal Pilim-1 administration at a dose of 20 mg/kg improved microcirculation in the rat skin, as judged by significant effects on perfusion and the amplitudes of the isolated rhythms of the LDF-gram. In addition, Pilim-1 exerted a moderate bacteriostatic and fungistatic activity, which was 2 times greater than the antimicrobial activity of Metronidazole. Conclusion: Topical application of gels containing 1% N-alkenylimidazole zinc complex derivatives accelerates the healing of uninfected linear and planar wounds in comparison with the established reference drugs. The Pilim-1 zinc compound exhibited the most pronounced therapeutic effect. The observed in vitro antimicrobial action of Pilim-1 is of further interest for potential implications in treatment of infected skin wounds. The regenerative effect of this substance opens prospects for development of new drugs with improved wound healing properties.